Analysis of Inventory Accounting Information System Model for Sustainability of Pontianak City Culinary SMEs - Sara, Emelda; Riyansah, Riyansah; Putra, Redius Sano; Widyastuti, Reni Dwi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
The purpose of this study was to determine the system of receiving, issuing inventory from the central warehouse to the outlet, to determine the system of receiving raw materials and supporting materials at the outlet and the restaurant's main warehouse, and accurate inventory information can encourage business decision making for inventory investment to be efficient and effective so that the business can survive and grow. This research uses a qualitative descriptive method on Culinary SMEs in Pontianak City. The data collection techniques that researchers use are observation, interview, and documentation techniques. The data analysis tool used to support this research is a flow chart from warehouse to outlet. The use of an Accounting Information System can automatically calculate and update EOQ and ROP based on actual sales and demand data so as to provide an integrated solution to inventory management problems from outlets to headquarters. With standard forms facilitating the flow of goods and orders, this model helps management to maximise inventory investment effectively and efficiently. This has a positive impact on timely order fulfilment, increasing outlet sales and revenue, and supporting the sustainability and development of SME culinary businesses. Overall, the implementation of this system encourages management effectiveness and increases profits by maintaining customer satisfaction. This research resulted in a flowchat Accounting Information System model with oulets consisting of outlets to the head office, and using Road Letter forms, Goods Request Letters, Goods Receipt Reports, Raw Material Inventory Cards, and Helping Material Inventory Cards.